Modified ionic liquid cold-induced aggregation dispersive liquid-liquid microextraction combined with spectrofluorimetry for trace determination of ofloxacin in pharmaceutical and biological samples - Zeeb, M. (Tehran University of Medical Sciences, 2011)
BACKGROUND AND THE PURPOSE OF THE STUDY: Ofloxacin is a quinolone synthetic antibiotic, which acts against resistant mutants of bacteria by inhibiting DNA gyrase. This antibacterial agent is widely used in the treatment of respiratory tract, urinary tract and tissue-based infections, which are caused by Gram-positive and Gram-negative bacteria. In this work, an efficient modified ionic liquid cold-induced aggregation dispersive liquid-liquid microextraction (M-IL-CIA-DLLME) was combined with spectrofluorimetry for trace determination of ofloxacin in real samples. METHODS: In this microextraction method, hydrophobic 1-hexyl-3-methylimidazolium hexafluorophosphate ([Hmim] [PF(6)]) ionic liquid (IL) as a microextraction solvent was dispersed into a heated sample solution containing sodium hexafluorophosphate (NaPF(6)) (as a common ion) and the analyte of interest. Afterwards, the resultant solution was cooled in an ice-water bath and a cloudy condition was formed due to a considerable decrease of IL solubility. After centrifuging, the enriched phase was introduced to the spectrofluorimeter for the determination of ofloxacin. RESULTS AND MAJOR CONCLUSION: In this technique, the performance of the microextraction method was not influenced by variations in the ionic strength of the sample solution (up to 30% w/v). Furthermore, [Hmim][PF(6)] IL was chosen as a green microextraction phase and an alternative to traditional toxic organic solvents. Different parameters affecting the analytical performance were studied and optimized. At optimum conditions, a relatively broad linear dynamic range of 0.15-125 µg l(-1) and a limit of detection (LOD) of 0.029 µg l(-1) were obtained. The relative standard deviation (R.S.D.) obtained for the determination of five replicates of the 10 ml solution containing 50 µg l(-1) ofloxacin was 2.7%. Finally, the combined methodology was successfully applied to ofloxacin determination in actual pharmaceutical formulations and biological samples.